PENGARUH CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Titus Bayu Santoso; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of corporate governance on tax avoidance. Corporate governance is proxied by the number of commissioners, the percentage of independent commissioner, compensation commissioners and the board of directors and stock ownership by the public. Tax avoidance is measured by the size of the book tax gap.This study used a quantitative research design and secondary data from companies listed in Indonesia Stock Exchange. By using purposive sampling in the observation period 2011-2013, obtained 60 observations. Data were analyzed using ordinary least squares regression models. Regression results show that the amount of salary compensation commissioners and board of directors have a positive and significant impact on tax avoidance. While the number of commissioners, the percentage of independent commissioners, and the public shareholding does not have a significant effect on tax avoidance. The results of this study indicate that some corporate governance mechanisms in Indonesia has not been effective according to its function for shareholders.